The Effect of Internal Control Entities to Determining the High of Audit fee - Winra, Nuryadi; Pontoh, Grace Theresia (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2021)
This research aimed to find out direct effect of the internal control entities to determining the high of audit fee, and indirect effect of the internal control entities to determining the high of audit fee through the extensive of auditor’s occupation. Data collection in this research used questionnaire which distributed to auditors who working in public accounting in Makassar. Analysis of the data used path analysis. The results of this research provided evidance that the internal control entities (X) had a significant direct effect to determining the high of audit fee (Y), and the internal control intities (X) had a significant indirect effect through the extensive of auditors’ occupation (M) to determining the high of audit fee (Y). The implication is if internal control entities is ineffective, it will be effect the larger of the extensive of auditor’s, so it will be also effect to the highest of amount in determining audit fee.